INCREASING THE RELIABILITY OF REMOTE METHODS FOR MEASURING THE TEMPERATURE OF THE SURFACE OF THE HUMAN BODY: Array - Krainiuk, O.; Buts, Yu.; Barbachyn, V.; Lotsman, P.; Kalchenko, D. (Municipal economy of cities. Series: «Economy science», 2021)
The aim of the work is to increase the reliability of remote methods of measuring the surface temperature of the human body. Common use of non-contact infrared (IR) devices for temperature screening. But it is important to pay attention to the accuracy of these systems to identify visitors or staff with an infectious disease. The following areas of improvement of metrological characteristics of non-contact devices for measuring human body temperature in a pandemic are identified: 15 cm, the presence in the equipment of a calibrated thermostable source of radiation, called the absolute black body (APT). An effective method of providing the most accurate measurements of skin surface temperature is associated with the use of "baseline sampling". To implement this method, a thermal imager measures the temperature of a specially selected group of perfectly healthy people, with whom the temperature of all others is compared. As a result of the conducted research the requirements to carrying out measurements of body temperature by IR thermometers for reception of reliable results are substantiated and offers on maintenance of these requirements for the purpose of increase of collective safety are put forward. It was found that the lack of calibration when measuring the body temperature of 50 university visitors with an IR thermometer is the cause of gross systematic error, which needs to be corrected by correcting. To increase the reliability of measurements, it is necessary to develop and test a simple and effective method of calibrating IR thermometers, suitable in normal operating conditions. Therefore, it is necessary to calibrate the IR thermometer before the measurements, which eliminates the systematic measurement error. The practical significance of the study is to determine the optimal conditions for the use of the device for non-contact temperature screening in a pandemic. The results of the work will be useful both for further study of increasing the reliability of the results of remote temperature measurement, and may be useful in the learning process.